Monitoring The Effort Curve In Physical Education For Normal And Overweight Students Using Smartwatches And Mobile Applications - Carmen, Pârvu; Dănuț, Mocanu George; Neculai, Harabagiu; Constantin, Ungurean Bogdan; Alexandru, Szabo Dan (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. In physical education and sports lessons, correctly dosing effort is essential for optimising physical performance and adapting effort parameters, including breaks, in line with physiological principles. The study hypothesises that using smart-watches and mobile apps to monitor effort in middle school physical education lessons will reveal significant differences in effort and heart rate between overweight and average BMI students. Modern technology is expected to enhance understanding of students’ physical exertion, facilitating adjustments to programs based on health status and fitness level. Material and method. The study involved 45 students (average age 13.5 years) using 15 Xiaomi 8 smart-watches, phones, Wi-Fi, the Mi Fit app, and other devices to analyse body composition. Data on heart rate and BMI were collected during lessons, which followed the same theme and effort dosage. The Mi Fit app provided detailed aerobic and anaerobic exertion analyses. Parental consent was obtained, and data collection was done under routine lesson conditions. The technology aimed to improve performance and customise programs, offering a personalised approach to physical education. Real-time data transfer enabled accurate analysis of physical effort, promoting healthier lifestyles and better lesson adaptation by teachers. Results. A significant interaction between heart rate and BMI steps (p < 0.01) shows different cardiovascular adaptations to exercise based on BMI. MANOVA confirmed the significant impact of these variables on heart rate, and post hoc comparisons showed differences between weight categories, except between overweight and extremely obese groups. These results highlight the need to tailor physical education programs to BMI categories to optimise cardiovascular health and performance. Conclusion. Results suggest that monitoring the effort curve using modern technologies, such as smart-watches and mobile apps, provides valuable information for adjusting and optimising physical education lessons, especially for overweight and obese students.